2019
DOI: 10.12688/f1000research.15995.2
|View full text |Cite
|
Sign up to set email alerts
|

Virologic failure and HIV drug resistance on simplified, dolutegravir-based maintenance therapy: Systematic review and meta-analysis

Abstract: Background: Dolutegravir-containing maintenance therapy is a promising simplification strategy for virologically suppressed HIV-infected individuals. However, most of the available data to inform this strategy come from small, uncontrolled studies. We estimated the proportion of HIV-infected patients experiencing virological failure (VF) and developing drug resistance on dolutegravir (DTG)-based maintenance therapy. Methods: We searched Medline, Embase, Cochrane Central, Web of Science, and conference abstract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…Based on rates of virological failure, the use of DTG as a monotherapy for PLHIV is contra-indicated, whereas the evaluation of dual therapy options is ongoing (143) (reviewed in Ref. 144). Current guidelines recommend the use of DTG, BIC, or RAL with two NRTIs for most PLHIV (9,10).…”
Section: Mechanisms Of Hiv Resistance To Instismentioning
confidence: 99%
“…Based on rates of virological failure, the use of DTG as a monotherapy for PLHIV is contra-indicated, whereas the evaluation of dual therapy options is ongoing (143) (reviewed in Ref. 144). Current guidelines recommend the use of DTG, BIC, or RAL with two NRTIs for most PLHIV (9,10).…”
Section: Mechanisms Of Hiv Resistance To Instismentioning
confidence: 99%
“…44 This conclusion is consistent with a metaanalysis of studies reporting virological failure among virologically suppressed patients switched to DTG-based 2DRs, which demonstrated that the efficacy of DTG-based combination therapies was considerably higher than that of DTG monotherapy. 45 Importantly, >50% of those experiencing virological failure on DTG monotherapy developed resistance, whereas no treatment-emergent resistance was recorded in patients who received DTG-based 2DRs. 45…”
Section: Pharmacokinetic Forgivenessmentioning
confidence: 99%
“…45 Importantly, >50% of those experiencing virological failure on DTG monotherapy developed resistance, whereas no treatment-emergent resistance was recorded in patients who received DTG-based 2DRs. 45…”
Section: Pharmacokinetic Forgivenessmentioning
confidence: 99%
“…There have been promising results for dual‐therapy regimens containing 3TC and either bPIs or dolutegravir both for first‐line ART and for maintenance therapy. The potential vulnerability of these regimens to compromise by the M184V/I mutation is a source of concern, as bPI or dolutegravir monotherapy is known to be suboptimal, although there is some evidence that bPI + 3TC dual maintenance therapy is effective in PLHIV with the previous detection of M184V . Very few people in our data set were switched to monotherapy or dual therapy including 3TC or FTC following the detection of M184V/I, and so we were not able to evaluate 3TC/FTC use in this setting.…”
Section: Discussionmentioning
confidence: 99%